Why implementation gaps could undermine synthetic nucleic acid oversight - Gillum, David R.; Moritz, Rebecca L. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionRecent U.S. biosecurity policy has shifted from organism-level controls to sequence-level governance of synthetic nucleic acids in response to de novo genome synthesis risks, artificial intelligence assisted design, and globalized DNA/RNA manufacturing. While intended to strengthen safety and security, this shift risks overburdening under-resourced institutions and providing oversight that looks thorough on paper but delivers little added protection. This study examines the widening “implementation gap” between policy ambition and operational capacity.MethodsDrawing on practitioner experience and current literature, we analyzed policy frameworks, institutional practices, and case examples to identify structural challenges in sequence-level oversight. Particular attention was given to how definitions, regulatory triggers, and institutional resources interact in practice, creating gaps between policy intent and operational capacity. This mixed approach allowed us to capture the high-level design of oversight frameworks and the practical realities of their implementation across diverse institutional settings.ResultsWe found three core obstacles: ambiguous definitions of sequences of concern, fragmented and overlapping regulatory triggers, and underdeveloped institutional screening and review capacities. Ambiguity creates uncertainty about what should be flagged, while fragmented rules add redundancies without clarifying responsibility. Limited institutional resources further constrain effective oversight. These weaknesses produce overinclusive surveillance, inconsistent provider screening, unmanaged legacy construct inventories, and a lack of shared reference tools, straining resources without yielding proportional security benefits.DiscussionAligning oversight with real-world capacity is essential to avoid brittle and costly systems that deliver limited biosecurity benefits. We propose seven reforms to address the identified obstacles: functional risk tiering, federal investment in biosafety infrastructure, policy pilots and real-world testing, institutional certification pathways, adaptive governance cycles, pragmatic global harmonization, and coupling screening with operational safeguards. These measures reduce ambiguity, streamline fragmented rules, and strengthen institutional capabilities. Embedding implementer perspectives and calibrating oversight to realistic capacities will ensure that biosecurity systems remain credible, resilient, and effective in the synthetic nucleic acid era.